2013
DOI: 10.1585/pfr.8.1202104
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Direct Ion Heating in Double-Pulsing CHI in Helicity Injected Spherical Torus Plasmas

Abstract: Anomalous ion heating has been observed for the first time during flux/current amplification by doublepulsing coaxial helicity injection (CHI) in the helicity injected spherical torus (HIST) device. Doppler ion temperature increases significantly near the separatrix on the inboard side during the second CHI pulse, whereas electron temperature remains constant. The experimental results indicate that selective ion heating may be associated with viscous damping of poloidal flows driven by the CHI pulse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Thus, the receiving sensitivity and instrument broadening of the system were analyzed when the width of entrance slit is varied, and the optimal width where the receiving sensitivity is high and the instrument broadening is low was evaluated. The instrument broadening of conventional 1-m Doppler spectroscopic system with multichannel PMT is around 0.03 mm [1,8]. In Fig.…”
Section: Evaluations Of Receiving Sensitivity and Instrument Broadeningmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the receiving sensitivity and instrument broadening of the system were analyzed when the width of entrance slit is varied, and the optimal width where the receiving sensitivity is high and the instrument broadening is low was evaluated. The instrument broadening of conventional 1-m Doppler spectroscopic system with multichannel PMT is around 0.03 mm [1,8]. In Fig.…”
Section: Evaluations Of Receiving Sensitivity and Instrument Broadeningmentioning
confidence: 93%
“…It was confirmed that the instrument broadening changes linearly at a slit width over 0.05 mm, and the receiving sensitivity saturates at the entrance slit width of 0.08 mm and wider. The instrument broadening of conventional 1-m Doppler spectroscopic system with multichannel PMT is around 0.03 mm [1,8]. In order to compare the proposed system with the measurement result of conventional IDS system, the entrance slit width 0.08 mm was applied in this paper, so that the proposed system can obtain the similar instrument broadening as that of conventional system.…”
Section: Evaluations Of Receiving Sensitivity and Instrument Broadeningmentioning
confidence: 99%